Government Communication Through Fkub In An Effort To Overcome The Dynamics Of Ethnic Simalungun Identity In Pematang Siantar City - Chotibul Umam Sirait; Mailin Mailin; Winda Kustiawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Indonesia, built from and in diversity, has been an independent country for 74 years, but may still be in the process of becoming a nation. The process of inter-ethnic acculturation continues through inter-ethnic or religious marriages. Inter-religious harmony is a form of peaceful socialization born of tolerance for religious diversity. The city of Pematang Siantar has many groups consisting of ethnic Batak who inhabit the North Sumatra region, which is also known as the Pematang Siantar area, while religious groups come from Muslim, Christian, Chinese and Buddhist ethnicities. Researchers see the importance of examining how young people of various ethnic cultures identify themselves in the land of the Batak people and as Indonesians in constructing social identity as part of the Indonesian Nation, studies that are explored directly in communities with certain cultural settings will provide input on how identity is built so that psychological concepts are obtained that better describe behavior in local cultural settings. To find out government communication through Religious Harmony Forum (FKUB) communication in an effort to overcome the dynamics of ethnic simalungun identity in Pematang Siantar city. To find out the role in the implementation of government communication through communication of the Religious Harmony Forum (FKUB) in an effort to overcome the dynamics of Simalungun ethnic identity in Pematang Siantar City.To find out whether there is a risk if the government does not take part in efforts to overcome the dynamics of Simalungun ethnic identity in Pematang Siantar City. The research used in this study is qualitative (case study). The emergence of protests by ethnic Simalungun to the government (mayor) of Pematang Siantar, due to dissatisfaction with various City Government policies, especially in the field of culture, which are considered to have harassed Simalungun culture and ethnicity. The dynamics of Simalungun ethnic identity in the city of Pematang Siantar are shown by the increasing number of Simalungun elements, as well as non-Simalunguns who sympathize with the protests and demands of the Simalungun people. Simalungun ethnic identity allegedly did not get a harmonious position, treatment and involvement in the implementation of development in the city of Pematang Siantar